ANALYSIS OF THE EFFECTIVENESS OF COMMERCIALIZATION POLICY IN PRIVATE UNIVERSITIES IN INDONESIA - Sisca Eka Fitria; Pramudya Ibnu Subrata (ITB AAS Indonesia Surakarta, 2023)
Indonesia is a developing country where the country's income still depends on natural resources. This encourages the Indonesian government to advance the country by improving the quality of human resources to support economic growth based on a knowledge base economy. The form of contribution to the country made by M University as one of the private universities in Indonesia is with its vision of becoming a research and entrepreneurial university and making commercialization policies through three institutions, namely PPM institutions, international cooperation institutions, and science techno park institutions as the end of downstream research. The effectiveness of commercialization policies is an important key to the success of private universities in Indonesia in achieving their vision. The approach of this study is descriptive qualitative where primary data sources come from internal and external sources who know the commercialization process and ecosystem. The result of this study is the information of a new entity that emerged, namely PT. XY is one of the research commercialization downstream institutions. The results of the effectiveness analysis are effective from the point of view of the commercialization policy objectives, namely becoming a Research and Entrepreneurial University. Based on 4 indicators, implementation is classified as effective, but the availability of resources related to the policy is still less effective. Judging from the commercialization process, the commercialization policy cannot be analyzed in terms of its effectiveness target, because policies are still changing, and programs are still adjusting to conditions and situations.